Integration of sustainable agriculture and rural development issues in agriculture policy: Proceeding of the FAO/Winrock International Workshop on Integration of SARD Issues in Agricultural Policy, held in Rome, May 22-24, 1995 - FAO (Winrock International, 1996)
The objects of the papers were: To identify pertinent issues that needed to be integrated in agricultural policy analysis; to discuss how the SARD issues could be incorporated in the policy and planning framework; to identify what, in the way of economic policy for SARD, FAO and other development assistance agencies immediately promote in countries to improve integration of SARD concerns in policy analysis; to initiate development of a cooperative effort for testing and applying methods in development countries